THE WAY OF LIFE OF STUDENTS AS A PEDAGOGICAL VALEOLOGICAL PROBLEM (Education in the 21st Century, 2023)
Nowadays, after the post-war and coronary epidemic, many health-threatening problems have arisen in people's lifestyle, which has led to a gradual deterioration of health.  Among students, there is dissatisfaction with a decrease in working capacity, a decrease in memory, and concentration of attention. Currently, the most important pedagogical valeological task is to ensure a healthy lifestyle of students. The lifestyle of each student is formed under the influence of both objective and subjective factors. The objective conditions of a student's life during socialization exist independently of their consciousness, needs, and planned plans.  Objective socio-economic, socio-historical, socio-political conditions of work, life and recreation in the microenvironment play a decisive role in lifestyle planning.  The effectiveness of students' mental performance is directly proportional to, perhaps, the most accurate and sensitive of biological laws "instrument " - biological rhythms and puberty. At the same time, both physiological and ecological rhythms of the biological clock determine the mental performance of the student, as well as determine how to combine mental and physical work with the organization of rest, sleep. The discrepancy of biological, mental and social rhythms in the lifestyle of students leads to a decrease in mental performance, sometimes to the occurrence of diseases. The social rhythms of students no longer fit into the framework of biological rhythms and, above all, the rhythm of sleep and wakefulness.
Keywords: healthy lifestyle; fitness; health; illness; student; biological rhythms; sleep and wakefulness rhythm; mental health; biological clock